"Political … civil and domestic slavery": Harriet Taylor Mill and Anna Doyle Wheeler on marriage, servitude, and socialism. Issue 2 (4th March 2021) - McCabe, Helen
ABSTRACT: Harriet Taylor Mill and Anna Wheeler are two nineteenth-century British feminists generally over-shadowed by the fame of the men with whom they co-authored. Yet both made important and interesting contributions to political thought, particularly regarding deconstruction of (i) the patriarchal institution of marriage; and (ii) the current property regime which, in dominating workers, unfairly distributing the product of labour, and encouraging 'individualism', they believed did little to maximize the general happiness. Both were feminists, utilitarians, and socialists. How they link these elements is both interestingly similar, and interestingly different. This article has four aims. Firstly, to make a strong claim concerning their authorial hand in works often considered to be solely the work of their male co-author. Secondly, to sketch those co-authoring relationships, and consider whether Taylor and Mill may even have consciously constructed their early letters 'On Marriage' based upon what they knew of Thompson and Wheeler's relationship. Thirdly, to map out their shared (though not identical) claim that marriage was a form of slavery, and the proposals they offered to free women from the domination of patriarchal relationships. Fourthly, to explore the way in which both thought female emancipation would be most truly realized via cooperative socialism.